Entrepreneurship Networks in Italy The Role of Agriculture and Services - Gurrieri, Antonia Rosa.; Lorizio, Marilene; Stramaglia, Annamaria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
In light of the recent dynamics of the recession sparked by the global economic crisis, a roadmap for the growth and recovery of national economies is urgently needed. As such, this book focuses on the potential offered not only by the manufacturing sector but also by the agricultural and tertiary sectors. In fact, during the crisis these sectors demonstrated remarkable resilience in the Italian economy and there have even been positive trends in specific segments. This book points out how an exit strategy could be applied that involves all economic sectors and which can be replicated in various national economies.
Entrepreneurship and Network -- The New Path of Agriculture -- Tourism: A Service Sector.
Keywords: Economics; Industrial organization (Economic theory).; Regional economics; Farm economics; Environmental economics; Entrepreneurship; Economics/Management Science; Entrepreneurship; Industrial Organization; Agricultural Economics; Regional/Spatial Science; Environmental Economics